Comparison of Sutures and Cyanoacrylate Tissue Adhesives for Wound Repair in a Rat Model of Corneal Laceration - NUHOĞLU, FADİME; Nuhoglu, FADİME; ALTIPARMAK, Ugur E.; HAZIROLAN, Dicle O.; KASIM, Remzi; DUMAN, Sunay (My University, 2013)
Aims: The aim of the present study was to evaluate the cicatricial repair of a corneal artificial perforation in rats with 10-0 nylon suture, N-butyl-2-cyanoacrylate (NBCA) adhesive, or NBCA + methacryloxysulfolane (NBCA-MS) adhesive through microscopic and histological assays. Methods: Twenty Wistar rats were randomly divided into 4 groups each containing 5 rats: (1) control group (corneal trauma without suturing and tissue adhesives), (2) suture group, (3) NBCA group and (4) NBCA-MS group. A central full-thickness 2-mm laceration was performed in the left eyes of the studied rats in all 4 groups. The presence of corneal edema, corneal neovascularization and tissue adhesive/suture were evaluated. On the 21st day, the rats were sacrificed and histological examination was performed to determine irregularity of corneal layers, superficial epithelization, polymorphonuclear leucocytes and neovascularization. Results: Tissue adhesives were as effective as suturing in closing full-thickness corneal wounds and no difference in postoperative healing was observed clinically. As for the histological results, suture-treated eyes had persistent corneal irregularity that can limit visual acuity and may also lead to astigmatism. Conclusions: The use of tissue adhesives constitutes a viable alternative clinical procedure to conventional sutures. Possible influences on astigmatism are hypothetical, as no objective measure of astigmatism was performed in the test animals. Copyright (c) 2013 S. Karger AG, Basel